Effect of water deficit of Ultisols, Entisols, Spodosols, and Histosols on oil palm productivity in Central Kalimantan - Sukarman, Sukarman; Saidy, Akhmad R.; Rusmayadi, Gusti; Adriani, Dewi Erika; Primananda, Septa; Suwardi, Suwardi; Wirianata, Herry; Fitriana, Cindy Diah Ayu (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2022)
The same rainfall can cause different degrees of water stress depending on soil type, so the production response shown by plants can be different. This study is essential for growers, especially in predicting oil palm production based on water deficit for each soil type. The study was conducted on oil palm plantations in Central Kalimantan, Indonesia, with four soil types in 1,446.15 ha (40 blocks). The source of data collected from oil palm plantations included bunch number, average bunch weight, rainfall, and soil physical and chemical properties for the last 15 years (2007 - 2021). This experimental study used a two-stage cluster sampling method. The results showed that the best productivity, bunch number, and average bunch weight were found on Ultisols. The four soil types tested showed the same annual production distribution dynamic, but the response rate from each soil type showed differences. Entisols and Spodosols were more prone to drought stress due to water deficit than Ultisols and Histosols because of the differences in soil texture. Water deficit causes a decrease in oil palm productivity by 5 - 22% in the first year (Ultisols 12 - 22%; Entisols 12 - 22%; Spodosols 7 - 19%;  Histosols 5 - 15%) and 1 - 8% in the second year (Ultisols 3 - 7%; Entisols 2 - 4%; Spodosols 5 - 8%; Histosols 1 - 5%) compared to previous years production. A decrease in oil palm productivity occurs at 3 - 5 months (bunch failure phase), 1 year (abortion sensitive phase), and 2 - 2.5 years (sex differentiation phase) after a water deficit appears.